Sosialisasi Pengelolaan Pendapatan Rumah Tangga untuk Pencegahan Stunting di Desa Wera Kecamatan Pamona Puselemba Kabupaten Poso - Novi Maryama Lempao; Feliks Arfid Guampe; Mikhael Jibrael Balo; Septian Aditya Kolompo; Olvit Olniwati Kayupa; Join Hengkeng; Indra Eka Wardana Toii; Fredrik Bastian Kawani (Lembaga Pengembangan Kinerja Dosen, 2024)
Stunting is a health problem that is still a challenge in Indonesia, especially in areas with low economic conditions. One of the contributing factors is less than ideal parenting due to limited knowledge in managing household income to meet children's nutritional needs. This community service activity aims to improve housewives' understanding of financial management and the selection of nutritious food at low cost to support stunting prevention. This activity was carried out in Wera Village, Pamona Puselemba District, Poso Regency, involving seven families with stunted children, integrated health post cadres, and community leaders. The method used was practice-based training that included lectures, group discussions, household budget preparation simulations, and demonstrations of selecting nutritious food at low cost. Evaluation was carried out through pre-tests and post-tests, participatory observations, and activity documentation. The results of the pre-test and post-test showed an increase in participants' understanding by 75.7%, with an average score increasing from 45.8 to 80.5. The indicator with the highest increase was the ability to prepare a simple family budget (87.5%), followed by an understanding of the importance of balanced nutrition (70.0%) and the selection of nutritious food at low cost (70.8%). The response of the participants was very positive, shown by enthusiasm in the discussion and active involvement in the practice of preparing a budget and demonstration of selecting food ingredients. This activity succeeded in increasing household financial literacy and awareness of the importance of nutrition in the family. The practice-based approach has proven effective in improving participants' understanding and skills. For the sustainability of the program, further assistance and collaboration with posyandu cadres and the village government are needed to ensure sustainable implementation in preventing stunting.